2021
DOI: 10.3390/su132413645
|View full text |Cite
|
Sign up to set email alerts
|

Pessimistic Tone in Earnings Announcement and CSR Disclosure: Exploring the Interacting Role of CEO Busyness

Abstract: This study analyzes the relationship between the pessimistic tone in earnings announcements and CSR disclosures interacted by CEO busyness. This study used 191 observations from 74 firms listed on the Indonesia Stock Exchange and the Global Reporting Initiative (GRI) database from 2016–2019. Grounded in signaling theory, we hypothesize that a pessimistic tone in earning announcements will increase CSR disclosure. We also hypothesize that busy CEOs strengthen this relationship. We use the ordinary least squares… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…The control variables were selected based on previous research, including the number of directors (DIRSIZE) (Roiston & Harymawan, 2022), number of commissioners (COMSIZE) (Guan et al, 2016; Ningsih et al, 2021), and independent directors (INDCOM) (Muttakin et al, 2018) to represent good corporate governance. Firm size (FIRMSIZE) (Abdullah et al, 2023) and leverage (LEV) (Cahyono, Harymawan, & Kamarudin, 2023) were chosen to represent company characteristics, while return on assets (ROA) (Ningsih et al, 2021) and loss (LOSS) were selected as profitability ratios to represent company performance, as in Guan et al (2020). The definitions of the variables used in this study for further information are listed in Table 2.…”
Section: Data and Research Methodologymentioning
confidence: 99%
“…The control variables were selected based on previous research, including the number of directors (DIRSIZE) (Roiston & Harymawan, 2022), number of commissioners (COMSIZE) (Guan et al, 2016; Ningsih et al, 2021), and independent directors (INDCOM) (Muttakin et al, 2018) to represent good corporate governance. Firm size (FIRMSIZE) (Abdullah et al, 2023) and leverage (LEV) (Cahyono, Harymawan, & Kamarudin, 2023) were chosen to represent company characteristics, while return on assets (ROA) (Ningsih et al, 2021) and loss (LOSS) were selected as profitability ratios to represent company performance, as in Guan et al (2020). The definitions of the variables used in this study for further information are listed in Table 2.…”
Section: Data and Research Methodologymentioning
confidence: 99%
“…Centralization of decision-making power can facilitate CSR disclosure by group companies (Masud et al 2022). A pessimistic tone in the income statement in the Management's Discussion & Analysis (MD&A) is significantly and positively associated with CSR disclosure; busy CEOs strengthen these relationships (Ningsih et al 2021). Family firms are more likely to shift their focus on surplus management through CSR disclosure, although the level of family ownership plays a moderating role (Gavana et al 2017).…”
Section: Intrinsic Dynamics Of Esg Disclosurementioning
confidence: 99%
“…Further, Zhang et al (2020) reveal that CSR disclosure alleviates reputational damage, enhances legitimacy, and plays an insurance-like or value-protection role during crises. Furthermore, Ningsih et al (2021) demonstrated that CSR disclosure might be used to mitigate the negative tone in management discussion and analysis (MD&A) and unfavourable income statements and that overworked CEOs might employ this as a cover-up tactic. In support of this assertion, Doh et al (2016) found that multinational firms in emerging economies have turned to CSR reporting to legitimate themselves before their stakeholders.…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%